Explaining success and failures in PPP transport projects: an econometric approach - Trujillo, Lourdes; Inchausti-Sintes, Federico; Campos, Javier; Manrique-de-Lara-Peñate, Casiano (European Journal of Transport and Infrastructure Research, 2018)
There are a multitude of factors, both internal and external, that may affect the development and success of any transport project. ‘Success’ is both context-dependent and quite difficult to measure. This paper distinguishes between four types of ‘success’ variables: (lack of) cost overruns; (lack of) time delays; (ex-post) level of traffic; and (generated) revenues. Each variable is modeled in a binary way (using discrete choice models), with each model estimating the relevance of various explanatory factors on the probability of success. Internal factors are found to have the greatest effect on that probability, and PPP projects seem to be prone to budget overruns and delays. Governance factors, such as the tender process, renegotiations, and issues related to penalties, among others, can all produce complications. Since the public authority has control over most of these variables, these results could be used to improve the ‘success’ of these projects.